Room-temperature thermoelectric materials: Challenges and a new paradigm - Han, Zhijia; Li, Jing-Wei; Jiang, Feng; Xia, Jiating; Zhang, Bo-Ping; Li, Jing-Feng; Liu, Weishu (Journal of Materiomics, 2022)
Room-temperature thermoelectric materials provide promising solutions for energy harvesting from the environment, and deliver a maintenance-free power supply for the internet-of-things (IoTs). The currently available Bi2Te3 family discovered in the 1950s, still dominates industrial applications, however, it has serious disadvantages of brittleness and the resource shortage of tellurium (1 × 10−3 ppm in the earth's crust). The novel Mg3Sb2 family has received increasing attention as a promising alternative for room-temperature thermoelectric materials. In this review, the development timeline and fabrication strategies of the Mg3Sb2 family are depicted. Moreover, an insightful comparison between the crystallinity and band structures of Mg3Sb2 and Bi2Te3 is drawn. An outlook is presented to discuss challenges and new paradigms in designing room-temperature thermoelectric materials. [Display omitted] •Similarities between Mg3Sb2 and Bi2Te3.•Quasi “melting” of chemical bonds.•Zintl compounds for promising TE materials.